Media and Participatory-Driven Communication Strategies in Raising Public Awareness of River Rehabilitation - Heni Nuraeni Zaenudin; Ahmad Fahrul Muchtar Affandi; Kokom Siti Komariah; Bagus Aditya Susanto; Alwan Husni Ramdani; Arrafi Malika Ardy (Mediator: Jurnal Komunikasi, 2026)
River degradation poses a serious threat to ecological stability and global public health. While environmental awareness continues to grow, it is often not accompanied by commensurate concrete action. This study aims to identify factors that bridge the gap between awareness and action in river rehabilitation programs. Through a systematic literature review of 46 academic articles (2020–2025) grounded in the SMCR communication model, this study examines the mechanisms that translate awareness into collective action. Key findings reveal a "Participation Paradox". Developed countries employing sophisticated campaigns experience a larger awareness-action gap due to one-way communication practices. Conversely, developing countries are more successful because they employ a dialogic approach based on community and trust. The "collective storytelling" mechanism, pioneered by community leaders, has proven to be the most effective in converting awareness into concrete action because it fosters trust and shared agency. In conclusion, dialogue and trust are far more crucial than technological sophistication. Management institutions must shift their role from mere information disseminators to dialogue facilitators. This study encourages practitioners to adopt community-based strategies and engage local leaders as catalysts for behavior change for successful river restoration.